Expanding My "Default" Audience. (1st September 2022) - Wu, Christine
My short audio documentary pauses for a glimpse into the world of described video, also referred to as visual or audio description. I interview a few multitalented people about their experiences with audio description, all of whom with versatile and generative repertoire beyond the brief introductions that follow: Natalie Trevonne and Melissa Lomax, two blind fashion lovers hosting the Fashionably Tardy podcast; Christine Malec and J.J. Hunt, a blind arts and culture consultant and a professional audio describer hosting the Talk Description To Me podcast; and, Andy Slater, a legally blind musician and installation artist. How can film and video be better crafted with access in mind? Having completed the project, I reflect on my decision to focus on audio description and my current relationship to the creative process.